2023
DOI: 10.3389/fpsyt.2023.1142682
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of ketone bodies in the diagnosis and treatment of psychiatric disorders

Abstract: In recent times, advances in the field of metabolomics have shed greater light on the role of metabolic disturbances in neuropsychiatric conditions. The following review explores the role of ketone bodies and ketosis in both the diagnosis and treatment of three major psychiatric disorders: major depressive disorder, anxiety disorders, and schizophrenia. Distinction is made between the potential therapeutic effects of the ketogenic diet and exogenous ketone preparations, as exogenous ketones in particular offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 220 publications
0
8
0
Order By: Relevance
“…It has also been demonstrated previously that exogenous ketone supplements, such as ketone salts (KSs) and ketone esters (KEs), not only increase the blood levels of ketone bodies (ketosis) but also effectively decrease anxiety levels in different preclinical rodent models [3,[9][10][11][12][13][14][15]. Moreover, the connection between the ketone supplement-evoked increase in blood ketone body β-hydroxybutyrate (βHB) levels and anxiolytic effects was also confirmed [3,9,12,14,16].…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…It has also been demonstrated previously that exogenous ketone supplements, such as ketone salts (KSs) and ketone esters (KEs), not only increase the blood levels of ketone bodies (ketosis) but also effectively decrease anxiety levels in different preclinical rodent models [3,[9][10][11][12][13][14][15]. Moreover, the connection between the ketone supplement-evoked increase in blood ketone body β-hydroxybutyrate (βHB) levels and anxiolytic effects was also confirmed [3,9,12,14,16].…”
Section: Introductionmentioning
confidence: 63%
“…It has been demonstrated that up to one-third of the population can be affected by anxiety disorders during their lifetime [1][2][3]. However, our knowledge about the mechanism of action of anxiety disorders is far from complete [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, diabetes in animals can impair novel spatial and object recognition as well as performance in Barnes, Morris watermaze, and active-avoidance foot-shock tasks, aspects of which may be correctable with glycemic control [42][43][44] . However, glucose is not the only fuel available to the brain; the brain can also utilize ketones as a fuel source, although this switch in metabolism requires mitochondrial adaptations, some of which have been linked to changes in motivated behavior 2,45,46 . More recent work has implicated glucose-independent roles of insulin function directly in the central nervous system [10][11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been posited that the production of ketone bodies derived from a ketogenic diet may act as glutamate inhibitors in the NMDA extrasynaptic receptor, decreasing inflammation and oxidative stress ( 93 ). Nevertheless, more evidence-based research is needed before determining whether adherence to ketogenic diets reduces the risk of dementia ( 85 , 94 ) and psychiatric diseases ( 93 , 95 ).…”
Section: Diets Beneficial For Patients With Alzheimer’s Dementiamentioning
confidence: 99%